2022
DOI: 10.1007/s12032-022-01705-z
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and cytotoxic effects of bioactive compounds isolated from Onosma bourgaei

Abstract: Onosma species have been used commonly for traditional medicine for years due to their bioactive compounds content. Onosma bourgaei aerial part was extracted with hexane and methanol successively. The methanol extract was subjected to chromatographic techniques to isolate allantoin (1), 3,4dihydroxybenzaldehyde (2), luteolin-7-O-glucoside (3), apigenin-7-O-β-glucoside (4), diosmetin-7-O-βglucoside (5), rosmarinic acid (6), globoidnan A (7). The structure of isolated compounds were identi ed by spectroscopic te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…The significant biological activity of OME was linked with the plant's antioxidant potential (1.12-2.33 mg/mL) possessed by its phytochemical contents, alkaloids (78.77%) and steroids (11.48%), especially 5,8-dihydroxy-2-(4-methylpent-3-enyl) naphthalene-1,4-dione, 3-O-Methyl-d-glucose, and β-Sitosterol as shown by the GC-MS analysis [16]. Similarly, researchers have shown experimental data results on the anticancer activity of Onosma species, Onosma stellulata [27], Onosma bracteata [15], and Onosma bourgaei [14]. Previously, scientists have shown the anticancer potential (against HCT 116 cell) of naphthoquinone (β-hydroxyisovaleryl shikonin) at the sub-G1 phase through its facilitating roles in the production of the reactive oxygen species (ROS) and inducing cancer cell apoptosis by caspase8/9 stimulation [28].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The significant biological activity of OME was linked with the plant's antioxidant potential (1.12-2.33 mg/mL) possessed by its phytochemical contents, alkaloids (78.77%) and steroids (11.48%), especially 5,8-dihydroxy-2-(4-methylpent-3-enyl) naphthalene-1,4-dione, 3-O-Methyl-d-glucose, and β-Sitosterol as shown by the GC-MS analysis [16]. Similarly, researchers have shown experimental data results on the anticancer activity of Onosma species, Onosma stellulata [27], Onosma bracteata [15], and Onosma bourgaei [14]. Previously, scientists have shown the anticancer potential (against HCT 116 cell) of naphthoquinone (β-hydroxyisovaleryl shikonin) at the sub-G1 phase through its facilitating roles in the production of the reactive oxygen species (ROS) and inducing cancer cell apoptosis by caspase8/9 stimulation [28].…”
Section: Discussionmentioning
confidence: 84%
“…The genus Onosma is a group of well-known traditional medicinal plants that contain numerous phytochemicals offering different bioactivity against a wide range of moderate and severe human diseases [12,13]. The identified phytochemicals (rosmarinic acid, apigenin-7-O-β-glucoside, and globoidnan A) from O. bourgaei showed significant anticancer efficiency against human colorectal adenocarcinoma HT-29 and human mammary gland adenocarcinoma MCF-7 cells [14]. Furthermore, O. bracteata Wall was identified with different phytochemicals (1,2-benzene dicarboxylic acid and bis (2-methyl propyl) ester) and its aerial part extracts were found to be significant growth inhibitors of human lung carcinoma A549 cell, human osteosarcoma MG-63, and human neuroblastoma IMR-32 [15].…”
Section: Introductionmentioning
confidence: 99%
“…For the past decades, several studies have confirmed the traditional usage of the Onosma species as cytotoxic agents, and mammalian cancer cell division was inhibited by its extracts and isolated compounds [45,55,60].…”
Section: Cytotoxicity Activitymentioning
confidence: 97%
“…The methanol extract of O. mutabilis aerial parts indicated significant anticancer activity against prostate (DU-145), mammary (MCF-7), and cervical cancer (Hep2c) cells with IC 50 values as 35.67 ± 0.15, 28.79 ± 0.23, and 41.83 ± 0.21 µg/mL, respectively [55]. The crude extracts of O. aucheriana showed significant cytotoxicity activity against human rhabdomyosarcoma, human cervix carcinoma Hep2c, and from murine fibroblast (L2OB) cell lines with IC 50 values range between 25.54 to 50.57 µg/mL [45].…”
Section: Cytotoxicity Activitymentioning
confidence: 99%
“…The anti-proliferative ability of RA was improved at lower concentrations in combination therapy [ 11 , 101 ]. RA behaved the excellent anti-proliferative activity against HeLa, HT29, A549 and MCF6 cancer cell lines with the IC 50 values of 249.80, 277.85, 241.47, and 220.25 µM [ 102 ]. EGFR is a primary target of the anti-proliferation effects of RA [ 80 , 101 ].…”
Section: Biological Processes and Mechanism Of Action Of Ra In Tumor ...mentioning
confidence: 99%